Only love can hurt like this [large type] - Toon, Paige, 1975- (Wheeler large print hardcover series., 2023)
When Wren realises her fiancé is in love with someone else, she thinks her heart will never recover. On the other side of the world, Anders lost his wife four years ago and is still struggling to move on. Wren hopes that spending the summer with her dad and step-family on their farm in Indiana will help her to heal. There, amid the cornfields and fireflies, she and Anders cross paths and their worlds are turned upside-down again. But Wren doesn't know that Anders is harbouring a secret, and if he acts on any feelings he has for Wren it will have a serious fall-out for everyone.